Gubernaculum Sparing Laparoscopic Orchiopexy in Cryptorchidism with Ipsilateral Congenital Absence of the Vas Deferens: Unique Outcome - Ebtehal Althobaiti; Hattan Badr; Maryam Aloqalaa; Raghdah Alsharif; Naif Alqarni (Case Reports in Urology)
Congenital absence of the vas deferens (CAVD) is an uncommon anomaly that occurs in up to 1% of the male population. It can be associated with various other anomalies, including cryptorchidism and renal anomalies, such as renal agenesis. We here present a case of cryptorchidism with ipsilateral congenital absence of the vas deferens and renal agenesis and used the Stephen-Fowler technique for Orchiopexy depending on gubernacular vessels. A 7-month-old boy was referred to our center with left grade 2 hydronephrosis, right renal agenesis, and right impalpable, undescended testis. Examination under anesthesia and laparoscopic exploration with staged Stephen-Fowler orchiopexy were performed. The patient was followed up at 3, 6, and 12 months and had an excellent outcome. Cryptorchidism with congenital ipsilateral absence of the vas deferens and renal agenesis is a rare diagnostic entity. Our case supports the suggested theory that the gubernacular vessels can increase the blood supply to the testis, although further studies are needed to confirm this hypothesis.